Influence of fiber content on rheological and mechanical properties of pineapple leaf fibers‐polypropylene composites prepared by twin‐screw extrusion. Issue 12 (6th June 2019) - Berzin, Françoise; Amornsakchai, Taweechai; Lemaitre, Alain; Castellani, Romain; Vergnes, Bruno
Abstract: Pineapple leaf fiber (PALF) is an agricultural waste that could be used as a reinforcing fiber for thermoplastic polymers. Therefore, it is important to characterize the properties of these composites. In this paper, PALF was used to prepare polypropylene‐based composites by twin‐screw extrusion. The objective was to evaluate the influence of the fiber content (between 10 and 30 wt%) on the rheological and mechanical properties of the composites. Variations in fiber dimensions (length, diameter, aspect ratio) along the screws were analyzed and revealed limited degradation in the tested condition. The rheological behavior of the composites was directly impacted by the fiber content, with a regular increase of the viscosity and the development of a melt yield stress above 20 wt% PALF. The mechanical properties showed an increase in Young's modulus (+115% at 30 wt% PALF) and stress at break (+72% at 30 wt% PALF), proportional to the fiber content, but a sharp decrease in elongation at break (from 980% to 10% at 30 wt% PALF). These results confirm that the fiber content is the main parameter controlling the rheological and mechanical properties of the PALF/PP composites and that this fiber from agricultural waste can be considered as a good candidate for various applications of PP‐based composites.